Methodische Evaluation von Verfahren zur Korrektur atmosphärischer Turbulenz in Bildsequenzen - Hübner, Claudia Susanne (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2024)
For long horizontal propagation distances, it is the atmosphere, not the sensor technology which is responsible for the quality of acquired image data. Atmospheric turbulence causes increased blur, reduced (color) contrast and (apparent) image motion, as well as image deformation. This work addresses the question of how best to mitigate these degrading effects and improve image data quality using suitable reconstruction techniques.